The Harmony of Multifaith Community and Government: A Study of The Role Of The FKUB In Riau - K. Khotimah (Asia-Pacific Journal on Religion and Society, 2021)
This paper examines the role of the FKUB in creating religious harmony in society. Beginning with the presentation of the importance of religious studies to create a conducive atmosphere that is tolerant, this research is focused on the description of institutions followed by the evaluation of FKUB's performance in creating religious harmony in Kampar District and Pekanbaru City. The findings obtained were, although FKUB's age was still two years old, its role or performance was quite significant.